Removal of Cr(VI) from Aqueous Solution Using A new Adsorbent - SUHAD A. YASIN; BANN A. DAWOOD (College of Education for Pure Sciences, 2013)
Abstract: In the present study, Cinnamon (which is locally known as darseen) from local market was used as new adsorbent for removal of Cr (VI)from aqueous solution after it is collected. The research including study of the effect pH, initial Cr(VI) concentration, adsorbent dose and contact time on the adsorption capacity and percent removal were explored. The equilibrium data were tested using several isotherm models, Langmuir, Freundlich and Tempkin equations. The adsorption isotherm fit well with all models studied and the maximum adsorption capacity Qm of different adsorbent dosage was (13.8mg/g), obtained from Langmuir model. When the experimental data were applied to the first-order, second-order and Elovich kinetic model, it was clear that second-order and Elovich models fitted well. KEYWORDS: Cinnamon, kinetic, Isotherm, Adsorption